Political communication on Facebook and populism. The 2019 European Parliament election in Spain (Communication & Society, 2022)
Populist actors have more success than other parties on social media –particularly Facebook– where their posts receive higher levels of engagement. The entry of populist parties onto the Spanish political stage can spread the use of their rhetoric and influence citizens’ political decisions, affecting the configuration of supranational institutions such as the European Union. The aim of this study is to use a quantitative content analysis to verify the presence of populist discourse in the 844 messages published on Facebook by Spanish parties during the 2019 European Parliament election campaign and to analyse their impact on user interaction. The results show that the newest and most extremist parties monopolise the messages with empty, anti-elite populism. However, the use of exclusionary populist discourse is also detected in more moderate conservative parties. Populist parties, especially VOX, lead user interactions, irrespective of whether the populist style appears in the messages. The results of the research show that the populist style is inexorably consolidating in Europe as an electoral communications strategy on Facebook. As with other European countries, extremist and opposition parties also adopt the populist style as a communications strategy. The results suggest that the success of populist actors on social media may be conditioned by the populist attitudes of their followers and less by the characteristics of these parties’ publications.